National University of Costa Rica and Its Regional Campuses as a Mechanism for Social Inclusion - Schmidt-Fonseca, Ileana (2016)
The Interdisciplinary Academic Program of the National University is developing the experience of systematizing the academic management processes in the Huetar Norte and Caribbean Region in order to understand whether the actions taken have reached the population with fewer opportunities of access to higher education; and thus to comply with the basic principles of the institutional mission. The results of the experience showed that 50% more of the institutional average of students from rural schools, CINDEAS, or telesecundaria (distance education secondary school), i.e., schools classified as stratum 3, were covered; besides, 89% of this population requires some type of socio-economic assistance to give them the opportunity to study. Therefore, a reviewing process of the statistics offered by the Student Statistics System and Student Life between the years 2009 to 2013 was launched to compare them with the institutional averages, and to know whether the academic action the National University developed in the regions is an efficient mechanism for social inclusion, as shown in the results initially obtained in the program. It turned out that, in the regional campuses, the average of coverage was 25% greater than the institutional average of students of stratum 3, a student population with socio-economic needs exceeding the institutional average as well. This allowed us to conclude that one of the mechanisms to ensure social inclusion at the National University is its action through the regional campuses.